Cartilage tissue engineering : exploring the potential of poly (lactic-co-glycolic acid) based scaffolds and the bioethical aspect from Islamic perspective - Rozlin binti Abdul Rahman (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2016)
Treating articular cartilage defect remains a major orthopaedic predicament. Being a simple structure that is avascular and aneural, articular cartilage has little ability to repair itself when damaged. Cartilage tissue engineering provides an alternative technique for restoring and regenerating damaged cartilage tissues. This study attempts to (1) evaluate and compare the growth of bone marrow mesenchymal stem cells (BMSCs) aspirated from rabbits' iliac crest and femur in two different culture media; α-Minimum Essential Medium (α-MEM) and a mixture of 1:1 Ham's F12 Nutrient Mixture (F12) and Dulbecco's Modified Eagle Medium (DMEM) or FD, (2) to evaluate the in vitro and in vivo cartilaginous tissue formation using BMSCs-seeded poly(lactic-co-glycolic acid) PLGA/Fibrin scaffolds and (3) to explore the bioethical issues within the Islamic perspective in relation to tissue engineering and regenerative medicine (TERM). Growth kinetic assessments were performed on monolayer-cultured BMSCs harvested from two locations and cultured in two different media. Constructs fabricated from BMSCs seeded onto PLGA/Fibrin were cultured for three weeks and thereafter were implanted in rabbit model. The in vitro cartilaginous engineered constructs were evaluated by gross inspection, cell proliferation assay, gene expression, sulphated glycosaminoglycan (sGAG) production and histology at week 1, 2 and 3 while the in vivo construct were harvested at week 6 and week 12 post-implantation. It was observed that BMSCs harvested from the iliac crest region and cultured in FD significantly promoted BMSCs growth. The in vitro study showed that after 3 weeks of culture, the PLGA/Fibrin construct exhibited significantly higher cell viability, higher sGAG content and better histo-architecture and cartilaginous extracellular matrix (ECM) compound in concert with the positive glycosaminoglycan accumulation when compared to the PLGA only construct. Post implantation, the osteochondral defects treated with PLGA/Fibrin/BMSCs constructs showed better repair, more cartilaginous extracellular matrix, higher sGAG content, superior compressive strength and greater expression of chondrogenic marker genes than PLGA/BMSCs group. COL2A1 which is the specific cartilage marker, ACAN, COL9A1 and SOX9 genes were expressed both in the in vitro and in vivo. This study suggested that PLGA/Fibrin when seeded with pluripotent BMSCs that underwent optimum manipulation may serve as a prospective construct to be developed as functional tissue engineered cartilage. This study may also act as a platform to spark the initiative in integrating Islamic bioethics in providing “middle of the road” approach moderating between science and religion. Debates on TERM must comprise on religious and ethical view considering there are still many grey areas that requires Islamic input. Based from the Islamic perspective, scientific researches in TERM are permitted, as long as it is not a threat to human being and applied within the permissible limits described by the Shari'ah.